Patients' Perceptions of Integrated Care Among Medicare Beneficiaries by Level of Need for Health Services. (October 2022) - Song, Nancy; Frean, Molly; Covington, Christian T.; Tietschert, Maike; Ling, Emilia; Bahadurzada, Hassina; Kerrissey, Michaela; Friedberg, Mark; Singer, Sara J.
Requirements for integrating care across providers, settings, and over time increase with patients' needs. Health care providers' ability to offer care that patients experience as integrated may vary among patients with different levels of need. We explore the variation in patients' perceptions of integrated care among Medicare beneficiaries based on the beneficiary's level of need using ordinary least square regression for each of four high-need groups: beneficiaries (a) with complex chronic conditions, (b) with frailties, (c) below 65 with disability, and (d) with any (of the first three) high needs. We control for beneficiary demographics and other factors affecting integrated care, and we conduct sensitivity analyses controlling for multiple individual chronic conditions. We find significant positive associations with level of need for provider support for self-directed care and medication and home health management. Controlling for multiple individual chronic conditions reduces effect sizes and number of significant relationships.